2002
DOI: 10.1097/00001648-200201000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Sunshine in the Triggering of Suicide

Abstract: Several reports indicate that suicide follows a seasonal pattern with a dominant peak during the month of maximum daylight. The purpose of this study was to evaluate the hypothesis that sunshine exposure may trigger suicidal behavior. We found a remarkably consistent pattern of seasonality with peak incidence around June in the northern hemisphere and December in the southern hemisphere. Moreover, there was a positive association between the seasonal amplitude of suicide (measured by relative risk) and total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
1
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 24 publications
12
103
1
20
Order By: Relevance
“…4,5 Although few studies have addressed this issue in the Southern Hemisphere, their fi ndings were similar. 2 They have shown that higher suicides rates occur during months with more daily sunlight hours.…”
Section: Descritoresmentioning
confidence: 72%
See 2 more Smart Citations
“…4,5 Although few studies have addressed this issue in the Southern Hemisphere, their fi ndings were similar. 2 They have shown that higher suicides rates occur during months with more daily sunlight hours.…”
Section: Descritoresmentioning
confidence: 72%
“…4,5 A less pronounced association was found in temperate zones, 2 and no association was seen in Singapore, located at the Equator line. 3 The present study data support the fi ndings of Chew & McCleary, 2 who compared suicidal behavior among 28 countries and concluded that seasonal variation in suicide is high in temperate zones (between 30° and 60° north and south of the Equator) and low in the tropics.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Seasonality was also observed for suicide with an increase in suicides rates in spring or early summer. This could be related to the seasonal mood disorders (Chew & McCleary 1995;Petridou et al 2002;Lambert et al 2003;Reutfors et al 2009). The aim of this study is to assess the prevalence of voluntary and involuntary admissions with particular reference to seasonality and clinical correlates, in a sample of patients consecutively admitted to our psychiatric unit during a period of 24 months.…”
Section: Objectivementioning
confidence: 99%
“…Les études médicales établissent fréquemment une relation entre le suicide et la dépression 1 et, de son côté, la biologie associe la dépression avec la mélatonine, une composante neurohormonale qui joue un rôle significatif dans la physiologie circadienne (Reppert et al, 1988 ;Kettl et al, 1997 ;Li et al, 2006). La rareté de la lumière dans les pays boréaux pourrait alors être associée aux taux élevés de suicide dans les pays comme la Finlande, le Danemark ou le Canada (Petridou et al, 2001). Dans tous les cas, la rythmicité saisonnière du suicide remet en question cette possibilité puisque que le taux de suicide augmente au printemps, alors que les journées se rallongent, et diminue en hiver lorsque les journées sont plus courtes.…”
Section: Les Rythmes Temporels Cosmobiologiquesunclassified